Empirical investigation on container port competition and cooperation - Aw, Bing Zong (2010)
For the past few decades, East and South East Asia container ports are slowly edging out Europe‟s and America‟s container ports to be the top 20 busiest container ports in the world. With the dawn of the financial downturn, container ports have to seize the opportunity to erode or match their competitors‟ competitive advantage or cooperate to remain competitive. Through empirical investigation and interviews with terminal operators, shipping lines and shippers, this paper aims to investigate the competitive factors in the current economic climate and the effect of sister-port agreements between container ports. Interviews and empirical investigations will reveal that ports‟ decisions are based on similar shipping dynamics with different emphasis on costs factors due to the current economic and competitive climate. Also, our cross examination in our data analysis will reveal the level of effectiveness that sister-port agreements amongst ports have on the ports overall throughout. This will be supported by our statistics gathered to prove the degree of complementarities among the sister-ports. Recommendations will also be highlighted along with limitations encountered throughout this empirical study as the conclusion is drawn.